PENDAMPINGAN LITERASI (BACA TULIS) USIA SEKOLAH DASAR DI RW 04 DESA KEDAWUNG - fathonah; Nur Ikhwan Rajabi; Abdul Latif; Hana Gardenia Mahbubah (Al Naqdu, 2023)
Reading and writing are vitals in the elementary school in an educated society and its needed a continuos efforts. Early observation in RT 02 RW 04 in the Kedawung Village, founded problems realated to elementary school are not yet fluent in reading, writing and recognizing the alpabhet. Problem solving with the implementation of individual assistance with “ pick up the ball” technique, with the implementation methods are observation, problem analysis process, making program design materials, evaluation of readiness, confirmation and shared perceptions with parents and implementation of assistance programs. The Stages of assistance are 1) introduction and strengthening of the alphabet, 2) random writing of the alphabet, 3) writing a series of words, 4) solving children’s problems, 5) random reading, 6) emotional approach sessions with children, and 7) evaluation at each assistance. The results of this assistance program have a positive impact on childrens can be more fluent in reading, writing, and recognizing the alphabet as well as increasing their motivations to learn.